2020
DOI: 10.5468/ogs.2020.63.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of vaginal misoprostol, laminaria, and extra amniotic saline infusion on cervical ripening and induction of labor

Abstract: Objective This study aimed to compare the effects of vaginal misoprostol, laminaria, and extra-amniotic saline infusion (EASI) on cervical ripening. Methods This randomized controlled trial was conducted on 195 women with singleton pregnancies and unripe cervices. Participants were randomly allocated to 3, 65-person groups: a misoprostol, a laminaria, and an EASI group. The interventions in the misoprostol, laminaria, and EASI groups included a single 25-µg vaginal misoprostol suppository, an intracervical lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…Dhakal et al also compared ICF and EASI for IOL and showed similar results in which 44 out of 50 patients in the ICF group and 42 out of 50 patients in the ICF and EASI group underwent successful labour. 28 The findings are comparable to our study where 42 /50 in group A and 44/50 in group B were delivered vaginally. Studies have also compared EASI with Prostaglandins and reported that 37% of women in EASI group achieved a Bishop Score of ≥ 8 at 8 hours as compared to 14% who received Prostaglandins .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Dhakal et al also compared ICF and EASI for IOL and showed similar results in which 44 out of 50 patients in the ICF group and 42 out of 50 patients in the ICF and EASI group underwent successful labour. 28 The findings are comparable to our study where 42 /50 in group A and 44/50 in group B were delivered vaginally. Studies have also compared EASI with Prostaglandins and reported that 37% of women in EASI group achieved a Bishop Score of ≥ 8 at 8 hours as compared to 14% who received Prostaglandins .…”
Section: Discussionsupporting
confidence: 88%
“…In many studies reported in the literature, all of the patients' babies were alive and healthy and none required NICU admission. 27,28,33,40,41 In contrast, in our study, a total of 8 patients required NICU admissions. The difference might be due to the setting of a public sector hospital in a developing country where due to lack of resources, increased burden on the doctors and staff, illiteracy, poverty, along poor sanitary conditions predispose the neonates to various infections and risk factors that lead to NICU admission.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…24,25 Hence, Foley catheter is a good method of induction of labor which is effective, safe, economical, easy to store, readily available, with less side effects. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies along with their positive effects, medicationbased therapies for CR also have adverse effects. These complications include perinatal and postnatal bleeding, prolonged labor, excessive stimulation of the uterus, fetal distress and injuries, nausea, vomiting, and fever (2,(12)(13)(14). Continuous professional training, especially in medicine, is changing and developing (15).…”
Section: Introductionmentioning
confidence: 99%